Personal relative deprivation increases self-selected portion sizes and food intake - Cheon, Bobby Kyungbeom (2019)
Cues and experiences of the deprivation of financial/material resources have been associated with increased caloric intake and risk for overweight/obesity. Given that social comparisons may serve as a powerful reference for the adequacy of one's standing and resources, the present research tested whether subjective feelings of personal relative deprivation (PRD) or “losing out” to others stimulates calorie selection and intake. Study 1 demonstrated that self-reported chronic experiences of PRD positively predicted calories selected for a portion and consumed during an ad-libitum meal. Study 2 revealed that experimentally-induced PRD resulted in an increase in the amount of calories selected on a portion selection task and a stronger desire to consume the foods. Consequently, these findings demonstrate that chronic and acute subjective deprivation of non-food resources may contribute to socioeconomic gradients in obesity, and that perceived social inequality may have inherently obesogenic properties that promote excess calorie intake.